2015
DOI: 10.1093/brain/awv133
|View full text |Cite
|
Sign up to set email alerts
|

Improving response inhibition systems in frontotemporal dementia with citalopram

Abstract: Disinhibition is a cardinal feature of behavioural variant frontotemporal dementia, arising from both frontal atrophy and serotonin depletion. Hughes et al. show that neurophysiological signatures of inhibition are reduced in frontotemporal dementia, and that citalopram rescues prefrontal neurophysiological deficits relative to placebo. Boosting serotoninergic transmission may facilitate management of disinhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 108 publications
2
74
0
1
Order By: Relevance
“…The mean plasma drug concentrations were 401.9 ng/mL after atomoxetine (range 31.7-889.0 ng/mL), 40.2 ng/mL after citalopram (6.6-70.3 ng/mL), and 0 ng/mL after placebo. The current range of plasma drug concentration was comparable to that in previous human studies using similar oral dose of atomoxetine [Chamberlain et al, 2009;Kehagia et al, 2014] and citalopram [Hughes et al, 2015]. The control subjects were tested without drug or placebo, to provide normative data on the task and imaging.…”
Section: Experimental Designmentioning
confidence: 73%
“…The mean plasma drug concentrations were 401.9 ng/mL after atomoxetine (range 31.7-889.0 ng/mL), 40.2 ng/mL after citalopram (6.6-70.3 ng/mL), and 0 ng/mL after placebo. The current range of plasma drug concentration was comparable to that in previous human studies using similar oral dose of atomoxetine [Chamberlain et al, 2009;Kehagia et al, 2014] and citalopram [Hughes et al, 2015]. The control subjects were tested without drug or placebo, to provide normative data on the task and imaging.…”
Section: Experimental Designmentioning
confidence: 73%
“…We found increased serotonin levels in FLTD (FC 10.71, p < 0.001). Central nervous serotonergic pathways are abnormal in FTLD [18] and serotonin reuptake inhibitors have been used as a symptomatic treatment in FTLD [19]. However, there is usually a limited exchange of serotonin across the blood brain barrier, and the significance of this peripheral serotonin result is unclear for the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited support for this approach from trials of selective serotonin reuptake inhibitors (SSRIs) in FTD where a systematic review and meta-analysis found that antidepressant treatment results in a 15.4 point reduction on the Neuropsychiatric Inventory with the strongest evidence for SSRIs, although acknowledging that the evidence was derived from small trials [53]. Furthermore, enhancing serotonergic transmission with citalopram may have an effect on response inhibition systems in FTD [54]. Trazadone is also well tolerated in people with neurodegenerative diseases [55,56] while Mirtazepine can promote sleep and the maintenance of weight which may be of benefit in PSP.…”
Section: Medicationmentioning
confidence: 99%